Improving the Sustainability of Road Management and Financing in Azerbaijan - World Bank (World Bank, Washington, DC, 2013)
A well-maintained road network that provides the level of service required by road-users is an important element of Azerbaijan's development strategy to accelerate economic growth and reduce poverty. As part of this strategy, the Government of Azerbaijan (Government) has undertaken major capital improvements on the major arterial road network. However, the secondary and local roads continue to be underfunded, and a large rehabilitation backlog has been accumulating in recent years. Deferred maintenance leads to a future burden of more expensive rehabilitation and road reconstruction: for every US$1 in deferred maintenance, there is an associated US$4 cost to road-users. To avoid such a scenario, the Government needs: (i) to devise an institutional and financing framework that provides adequate funding for maintenance and rehabilitation; and (ii) to finance capital improvements on key priority roads. The objectives of this study are: (i) to identify the weaknesses and challenges confronting the sustainability of road maintenance and rehabilitation; (ii) to determine to what extent these factors are linked to particular institutional and financing arrangements; and (iii) to assess how these factors can be resolved. The study makes a series of recommendations aimed at improving the management and financing of the road sector in Azerbaijan.